Determining factors related to the incidence of the tuberculosis in a municipality of Santiago de Cuba - Mayelin Marin Mendez; Arístides Ramón Rodríguez Julian; Laidelbis Minier Pouyou (Centro Provincial de Información de Ciencias Médicas, 2019)
Introduction: Tuberculosis is an infectocontagious disease that affects a great number of people worldwide.  Objective: To describe the characteristics of this disease in themunicipality ofMella, according to some social-demographic, social -cultural, social-behavioural, biological, environmental determinants as well as of health services and to identify the risk factors present in the community.   Methods: An ecological, cross sectional study with combined designs was carried out. The universe was constituted by the 7 cases notified with lung tuberculosis in themunicipality ofMella,Santiago de Cuba, from 2016 to 2018.   Results: Among the most affected risk groups we can mention: elderly, alcoholic, diabetics and undernourished adults; with more incidence in male sex. Among other findings, the possible associations between the incidence of tuberculosis and the risk factors were detected.   Conclusions: The rates of incidences were associated in a direct way to the populational density, overcrowding, little ventilation and scarce illumination.